2020
DOI: 10.1111/and.13797
|View full text |Cite
|
Sign up to set email alerts
|

Semen quality and freezability analysis during breeding and non‐breeding seasons in heavy draft stallions in southern Chile

Abstract: The aim of this study was to evaluate seasonal changes in basic parameters of sperm quality and freezability behaviour of ejaculates from 10 fertile heavy draft stallions. A total of 140 ejaculates were collected, processed and evaluated during both the breeding (September–November) and non‐breeding seasons (April–June). Fresh semen was evaluated for volume, concentration, total spermatozoa per ejaculate, plasma membrane integrity and total sperm motility. Cryopreserved samples were evaluated for plasma membra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 32 publications
1
5
0
Order By: Relevance
“…Also, it is believed that the adverse conditions within the uterus and oviduct are essential for selecting the most suitable sperm for fertilization [ 60 ]. Reports on stallions did not register differences in sperm TM during breeding and resting seasons [ 61 ], thus agreeing with the results obtained in this study. Several authors describe a positive effect of collection frequency in bull sperm TM [ 4 ], but, in our study, during the mating period, in which there is a higher ejaculation frequency, the opposite effect was observed, with bulls showing the lowest TM, which can be related to a high renewal rate and no adequate maturation of spermatozoa.…”
Section: Discussionsupporting
confidence: 92%
“…Also, it is believed that the adverse conditions within the uterus and oviduct are essential for selecting the most suitable sperm for fertilization [ 60 ]. Reports on stallions did not register differences in sperm TM during breeding and resting seasons [ 61 ], thus agreeing with the results obtained in this study. Several authors describe a positive effect of collection frequency in bull sperm TM [ 4 ], but, in our study, during the mating period, in which there is a higher ejaculation frequency, the opposite effect was observed, with bulls showing the lowest TM, which can be related to a high renewal rate and no adequate maturation of spermatozoa.…”
Section: Discussionsupporting
confidence: 92%
“…Whilst breed is not a direct measure of inbreeding, it was accounted for within the statistical model. Considering the method of breed categorisation, stallions were grouped using recognised methods (Ebel et al, 2020). However, differences in sperm trends may be on a more specific level, indicating a potential limitation of broad categorisation methods required in this data set.…”
Section: Discussionmentioning
confidence: 99%
“…Morte et al 8 reported differences in spermatic concentration, vitality and morphology, but the progressive motility did not differ among seasons. Recently, Ebel et al 9 evaluated seasonal changes in the quality of sperm from fertile stallions, and only viability showed higher values during the breeding season; Johannisson et al 10 found minor variations in kinematics and morphology of sperm among seasons.…”
Section: Introductionmentioning
confidence: 99%
“…Groups of proteins have been reported as associated with mammalian 19 and stallion reproductive capacity, such as fibronectin type II modules, cysteine-rich secretory proteins (CRISPs) and spermadhesins 16 , albumins and kallikreins 9 . In horses, different semen proteins have been reported for the breeding and non-breeding seasons 9 , 10 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation